Antibiotics-induced dysbiosis impacts dendritic morphology of adult mouse cortical interneurons - Mohammed M. Nakhal; Ayishal B. Mydeen; Lydia K. Yassin; Reem Almazrouei; Rasha Alkamali; Mahra Alsulaimi; Rawan I. Elsaleh; Shamsa BaniYas; Shaikha Al Houqani; Farah Al-Marzooq; Maya Hassane; Roman Voitetskii; et al. (Frontiers in Neuroanatomy, 2025)
IntroductionA growing body of evidence suggests that the gut microbiome may contribute to changes in brain morphology. The microbiota-gut-brain axis (MGBA) has been shown to influence neurogenesis, axon myelination, and synapse structure. However, it remains unclear whether the MGBA can influence the morphology and density of inhibitory GABAergic interneurons. The aim of this study was to determine whether antibiotic-induced dysbiosis (AID) is associated with alterations in dendritic morphology of GABAergic inhibitory interneurons in the medial entorhinal cortex (mEC), somatosensory cortex (SSC), motor cortex (MC), and hippocampus (Hp).MethodsA cohort of six-month-old GAD-67-EGFP transgenic mice was treated with an antibiotic cocktail for two weeks, resulting in gut dysbiosis as validated by collecting stool samples at baseline and after treatment, then using next-generation sequencing of 16S ribosomal RNA.ResultsThe results demonstrate that the proposed model effectively exhibited the defining features of gut dysbiosis, including a significant reduction in microbiome diversity, expansion of pathobionts, and loss of beneficial microbes. The AID group showed alterations in density and morphology of GABAergic interneurons in different brain areas. The mean dendritic length and mean dendritic segments of the SSC and Hp were found to be significantly decreased, while no such decrease was observed in the mEC or MC. Furthermore, the density of interneurons was decreased in the mEC, Hp, and SSC areas, while no change was observed in the MC area.DiscussionThe interneuron dysfunction plays a role in the pathogenesis of neurological disease. The findings of this study suggest that AID potentially influences the density and morphology of the interneurons, which may contribute to the development of neurological disorders.